Diagnostic colonoscopy completion after abnormal fecal immunochemical testing and quality of tests used at 8 Federally Qualified Health Centers in Southern California: Opportunities for improving screening outcomes. Issue 23 (3rd September 2019) - Bharti, Balambal; May, Folasade (Fola) Popoola; Nodora, Jesse; Martínez, María Elena; Moyano, Karina; Davis, Shauntay L.; Ramers, Christian B.; Garcia‐Bigley, Felipe; O'Connell, Shawne; Ronan, Kevin; Barajas, Melissa; Gordon, Sheree; et al.
Abstract : Background: The effectiveness of colorectal cancer screening with fecal immunochemical tests (FITs) of stool blood depends on high rates of colonoscopy follow‐up for abnormal FITs and the use of high‐quality tests. This study characterized colonoscopy referral and completion among patients with abnormal FITs and the types of FITs implemented in a sample of Southern California Federally Qualified Health Centers (FQHCs). Methods: FQHCs in San Diego, Imperial, and Los Angeles Counties were invited to define a cohort of ≥150 consecutive patients with abnormal FITs in 2015‐2016 and to provide data on sex, insurance status, diagnostic colonoscopy referrals and completion within 6 months of abnormal FITs, and the types (brands) of FITs implemented. The primary outcomes were the proportions with colonoscopy referrals and completion for all patients at each FQHC and in aggregate. Results: Eight FQHCs provided data for 1229 patients with abnormal FITs; 46% were male, and 20% were uninsured. Among patients with abnormal FITs, 89% (1091 of 1229; 95% confidence interval [CI], 0.87‐0.91) had a colonoscopy referral, and 44% (539 of 1229; 95% CI, 0.41‐0.47) had colonoscopy completion. Across FQHCs, the range for colonoscopy referral was 73% to 96%, and the range for completion was 18% to 57%. Six of the 8 FQHCs (75%) reported FIT brands with limited data to support their effectiveness. Conclusions: In a sample of Southern California FQHCs, diagnostic colonoscopy completion after abnormal FITs was substantially below the nationally recommended benchmark to achieve 80% completion, and the use of FIT brands with limited data to support their effectiveness was high. These findings suggest a need for policies and multilevel interventions to promote diagnostic colonoscopy among individuals with abnormal FITs and the use of higher quality FITs. Abstract : In a survey of 8 Federally Qualified Health Centers, among 1229 patients with an abnormal fecal immunochemical test for colorectal cancer screening, 89% had a referral, but just 44% completed diagnostic colonoscopy, with the range of completion rates ranging from 18% to 57% across health centers. The findings suggest a major need for policies and multilevel interventions to promote diagnostic colonoscopy among patients with abnormal colorectal cancer screening tests.